Constructing a living theory of change in fluid and volatile environments: Grounded on context, problem, and evidence - and Hassnain, Hur (Theories of Change in Reality, 2024)
Theory of change is an explicit articulation of how an intervention creates an intended result to address a specific problem. This ‘theory’ is difficult to re/construct if the ‘context’ is complex, conflict-ridden, and uncertain. In such contexts, causal linkages leading to a desired outcome tend to be messy, multilevel, multidirectional, and unpredictable, as plans and strategies often do not work as anticipated. Whilst some activities lead to outcomes, others do not. Outcomes (positive or negative) could also emerge in unexpected places. This essay discusses why and how evaluations in fluid and volatile environments must aim to tackle the emergence and unpredictability of outcomes, and re/construct a theory together with key stakeholders. This ensures that it is fully grounded in the context, problem, and available evidence at the inception stage of the evaluation process and onwards. Preferably, evaluators should be engaged from the design of the intervention and its theory of change because a lack of understanding of the context results in causing harm to individuals, groups, and organisations and creates a lack of realism about the capacity of external actors to support substantive positive change. A better understanding of the context can help illustrate the causal links, hypotheses, and assumptions that make evaluations reliable and safe for the enumerators, evaluators, and the affected population. It also aids in assessing whether the intervention has had a positive or negative effect or no effect at all.